2017
DOI: 10.1021/acs.chemmater.6b04990
|View full text |Cite
|
Sign up to set email alerts
|

Interface Stability of Argyrodite Li6PS5Cl toward LiCoO2, LiNi1/3Co1/3Mn1/3O2, and LiMn2O4 in Bulk All-Solid-State Batteries

Abstract: International audienceArgyrodite Li6PS5Cl is a good candidate for being a solid electrolyte for bulk all-solid-state Li-ion batteries because of its high ionic conductivity and its good processability. However, the interface stability of sulfide-based electrolytes toward active materials (negative or positive electrodes) is known to be lower than that of oxide-based electrolytes. In this work, we investigate the interface stability of argyrodite toward several positive electrode materials: LiCoO2, LiNi1/3Co1/3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
446
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 501 publications
(497 citation statements)
references
References 30 publications
30
446
0
1
Order By: Relevance
“…Such large interfacial impedance may originate from various factors such as non-uniform current distribution and poor physical contact between electrode material and electrolyte 13,39,40 . However, since carbon additives usually offer better current distribution in a cathode matrix, it is unlikely that the presence of carbon additives would increase the total impedance of composite cathode simply by inducing non-uniform current distribution 39 .…”
Section: Resultsmentioning
confidence: 99%
“…Such large interfacial impedance may originate from various factors such as non-uniform current distribution and poor physical contact between electrode material and electrolyte 13,39,40 . However, since carbon additives usually offer better current distribution in a cathode matrix, it is unlikely that the presence of carbon additives would increase the total impedance of composite cathode simply by inducing non-uniform current distribution 39 .…”
Section: Resultsmentioning
confidence: 99%
“…During cycling, the voltage was varied between 0.62 and 4.12 V vs. Li + /Li, far outside the narrow electrochemical stability window predicted for these sulfide electrolytes 40, 41 . Recently, it was demonstrated that charging up to similar potentials results in oxidation of argyrodite Li 6 PS 5 Cl toward elemental sulfur, lithium polysulfides, P 2 S x ≤5 and LiCl 61 . Based on this, we suggest that the increase in activation energy is a result of the formation of an interfacial layer of similar oxidation products from the Li 6 PS 5 Br solid electrolyte that develop during the first cycles.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Thus, SSBs have been focused on recently and many kinds of solid electrolyte have been developed, including polymer, [4] garnet, [5] argyrodite, [6] LISICON-type, [7] NASICON-type, [8] and Perovskite-type [9] structure. [3] Thus, SSBs have been focused on recently and many kinds of solid electrolyte have been developed, including polymer, [4] garnet, [5] argyrodite, [6] LISICON-type, [7] NASICON-type, [8] and Perovskite-type [9] structure.…”
Section: Doi: 101002/aenm201801528mentioning
confidence: 99%